ISONIAZID THE CULPRIT BEHIND TOXIC OPTIC NEUROPATHY - O, Balaji; B, DIPANJAN; P, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Literature regarding toxic optic neuropathy (TON) due to isoniazid (INH) is scarce. This diagnosis is often missed, leading to unnecessary delay in institution of corrective measures. Often, this delay can worsen the patient's vision, with a high likelihood of development of serious damage to the patient's vision. We report a case of a 49-year-old gentleman, afflicted with meningeal tuberculosis, who developed visual disturbances following the administration of antitubercular therapy. The patient's vision improved dramatically following INH's withdrawal. This case highlighted the need to keep INH as a possible cause for TON, especially if vision does not improve following ethambutol's withdrawal. Further, this case attests to the need for thorough and periodic visual examinations in patients receiving antitubercular therapy. Â 